SHIEBA: personal portable shield barrier / Nur Fatin Aniesya Azizul Aziz - Azizul Aziz, Nur Fatin Aniesya (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
2022, Covid-19 has become integrated into our lives at this point, and most daily activities have been allowed again, such as going out to places and dining in at restaurants. It is now our duty to protect ourselves from contracting the virus and slow down its transmission. SHIEBA is a personal health and safety product that specializes in protecting its users from airborne droplets. It is a personal portable shield barrier suitable for situations where they would have to take off their masks in public. Although restaurants have taken precaution by spacing out seats, customers still have to remove masks to eat. As we know, coughs and sneezes propel airborne droplets for large enough distances to reach other people at other tables. This product would allow people to dine-in without having to worry about this as the protective film not only stops the droplets from reaching the person, but also their food. SHIEBA utilizes features that make its usage simple and hassle free, which would be features such as portable, lightweight, and easy to clean The objectives of SHIEBA are (1) to provide a portable shield barrier for dine-in customers, (2) to be able to sanitize tables before seating, and (3) to be attachable and sturdy enough to provide adequate protection to the customer. A descriptive survey approach is used to acquire relevant information from the respondents regarding their habits involving self-hygiene and their practices when going out to restaurants.Based on these findings, they may give the product a chance, as long as the product does not become a hassle for them to use. It is hoped that, with this invention, users can freely dine-in at restaurants without having to put their health at risk.